Pengaruh rasa ingin tahu terhadap koneksi matematis siswa pada pembelajaran trigonometri menggunakan model kooperatif tipe Think Talk Write (TTW) di kelas X SMA Negeri 10 Banjarmasin tahun pelajaran 2016-2017 - Apriyanto Apriyanto; M. Royani; Muh. Fajaruddin Atsnan (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this study is to know the curiosity, the ability of mathematical connections, and whether or not there is a curiosity influence on students' mathematical connection ability in trigonometry learning using cooperative type think talk write (TTW) model in X-1 class SMA Negeri 10 Banjarmasin school year 2016-2017. The research method using descriptive research method. Population is the students of class X SMA Negeri 10 Banjarmasin year 2016-2017 lessons, amounting to 226 students. The sampling technique used cluster randomsampling. The sample in this study is the students of X-1 class of SMA Negeri 10 Banjarmasin, amounting to 36 students. Technique of collecting data using observation and test. Results of research on trigonometric learning using the think talk write (TTW) cooperative model in class X-1 SMA Negeri 10 Banjarmasin showed that: (1) Character of curiosity of students included in qualification already developed, (2) The ability of connection between mathematical concepts is included in good category, (3) There is influence of curiosity character to students' mathematical connection ability.